A Therapeutic Game for Sexually Abused Children and Adolescents (Vil Du?!): Exploratory Mixed Methods Evaluation - Joyce Johanna Endendijk; Henny Tichelaar; Menno Deen; Maja Deković (JMIR Publications, 2021)
BackgroundTalking about experiences of sexual abuse in therapy is difficult for children and adolescents. Possible reasons for this difficulty are a lack of vocabulary to describe the situation or feelings of shame, fear, and self-blame associated with sexual abuse. The serious game Vil Du?! was developed to help children open up about their sexual abuse experiences. Vil Du?! is a nonverbal communication game that resembles a dress-up game in which children can show the therapist what happened to them. ObjectiveThis exploratory evaluation study examines which working elements of the game could be identified in therapy with victims of sexual abuse (aim 1). In addition, this study examines how therapists evaluate the acceptability of the game (aim 2). MethodsThe therapists completed 23 web-based surveys on the use of Vil Du?! In addition, semistructured interviews were conducted with 10 therapists. The data were analyzed in NVivo following previously reported stepwise guidelines. ResultsRegarding aim 1, therapists mentioned various working elements of Vil Du?!; for instance, Vil Du?! puts the child in control of the situation. In addition, Vil Du?! reduces barriers to disclosure because there is no need to talk or have eye contact with the therapist. Regarding aim 2, Vil Du?! was generally evaluated more positively than negatively by the therapists. For instance, therapists indicated that using Vil Du?! is time efficient and might make the treatment process less confronting and difficult for the client. According to therapists, most clients indeed experienced less tension and more positive (or neutral) emotions than negative emotions when using Vil Du?! ConclusionsThe most important working elements of Vil Du?!, according to therapists, are that it enables children to regain control over their sexual abuse experiences and reduces barriers to disclosing sexual abuse experiences. The more positive evaluation of Vil Du?! indicates the acceptability of the game for therapists as well as their clients.